Public Health Response and Control Measures for Monkeypox Virus Outbreaks.” A review of past and present outbreak responses, highlighting successes, challenges, and lessons learned - Aziz, Mufakkir; Mohamad, Tasneem Noor; Wazir Ali, Hafeezullah; Awad Elsied, Manal Satti; Shah, Aamna; Asif, Muhammad; M. A. Dahesh, Salwa (Journal of Neonatal Surgery, 2025)
Monkeypox, an emerging zoonotic disease caused by the monkeypox virus, has become a major global public health concern due to its periodic outbreaks and expanding geographic reach. This review provides a comprehensive overview of public health responses to monkeypox outbreaks, focusing on the global rise in 2022 and the important 2024 outbreak. Drawing on epidemiological data, scientific literature, and public health reports, the review investigates the virus's origins, transmission dynamics, and clinical manifestations, as well as a chronological examination of its epidemiological patterns. Data for this review were gathered from a variety of sources, including historical outbreak records from endemic regions, World Health Organization (WHO) updates, national public health reports, and peer-reviewed studies, to highlight initial response measures such as quarantine, contact tracing, and public awareness campaigns. While such approaches have had various degrees of success, newer developments, such as the return of smallpox immunizations and antiviral medications like tecovirimat, have dramatically enhanced outbreak containment efforts. Enhanced surveillance systems and data-driven techniques have proven useful in detecting and managing epidemics. The obstacles, which ranged from vaccine inequities and misinformation to gaps in worldwide coordination, were particularly evident during the 2024 pandemic, when resource limits and public perception hampered effective control measures. Despite these challenges, important triumphs, such as community-led awareness campaigns and improved immunization regimens, are mentioned. This review highlights the necessity of long-term global collaboration, strong public health infrastructure, and continuous vaccination and medicines development. Lessons from the 2024 outbreak highlight the importance of data-driven measures and equitable resource allocation to prevent future outbreaks and protect world health.